2014
DOI: 10.1097/rlu.0b013e3182816515
|View full text |Cite
|
Sign up to set email alerts
|

Hypermetabolic Mesenteric Brown Adipose Tissue on Dual-Time Point FDG PET/CT in a Patient With Benign Retroperitoneal Pheochromocytoma

Abstract: Intense FDG uptake of the mesenteric brown adipose tissue (BAT) is rare. We present a case of benign retroperitoneal pheochromocytoma showing multiple hypermetabolic regions corresponding with common locations of BAT. Furthermore, the mesenteric region showed intense FDG uptake, with SUVmax of 10.6. FDG PET/CT findings of this case supports the previous theories that the incidence of BAT may be higher in patients with pheochromocytoma than in patients without, and the intra-abdominal fat of human adults, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Furthermore, in patients with retroperitoneal pheochromocytoma, abdominal visceral fat exposed to high noradrenaline concentrations for prolonged durations has shown intense 18 F-FDG uptake (27). These findings suggest that beige adipocytes may be of potential significance in human subjects, as they are in mice.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, in patients with retroperitoneal pheochromocytoma, abdominal visceral fat exposed to high noradrenaline concentrations for prolonged durations has shown intense 18 F-FDG uptake (27). These findings suggest that beige adipocytes may be of potential significance in human subjects, as they are in mice.…”
Section: Discussionmentioning
confidence: 69%
“…Images revealed primary lung malignancy with co existing bilateral renal tuberculosis imitate metastases which otherwise would have gone amiss or would have been considered as metastases without dual phase [14]. In a case report the authors found useful delayed images in a case of benign retroperitoneal pheochromocytoma showing multiple hypermetabolic regions corresponding with common locations of Brown adipose tissue [15].…”
Section: Discussionmentioning
confidence: 98%
“…The FDG uptakes of BAT commonly locate at the cervical, supraclavicular, paravertebral, mediastinal and perirenal region in adults, and the amount and extent of BAT decreases, even disappears with age from many areas including the omental and mesenteric regions [1]. However, previous case reports have observed the FDG uptake of mesenteric BAT in adult patients with catecholamine-secreting neoplasm such as pheochromocytoma or paraganglioma [2][3][4]. Their findings were based on the change of FDG uptake levels on dual-time point scans or after oral administration of β-adrenergic antagonist propranolol to patients.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Examples of relatively atypical locations for BAT include posterior neck, paratracheal and perirenal area [1]. Reports of the activation of BAT in the mesentery are rare and have lacked direct histological evidences [2][3][4].…”
Section: Unusual Fdg Uptakes Of Mesenteric Brown Adipose Tissue In a mentioning
confidence: 99%